1979
DOI: 10.1099/00221287-110-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Induced Quantitative Variation for Penicillin Titre in Clonal Populations of Aspergillus nidulans

Abstract: The variation in penicillin titre within populations of cultures of Aspergillus nidulans derived from untreated conidia and from conidia treated with ethyl methanesulphonate (EMS), near-ultraviolet light in the presence of 8-methoxypsoralen (8MOP) or N-methyl-N'-nitro-N-nitrosoguanidine (NTG), each at several dose levels, was determined. Both mutagentreated and untreated populations showed a continuous distribution of pencillin titres. The population mean titre of the mutagenized populations was decreased and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…Preliminary experiments designed to facilitate the choice of mutagen and mutation conditions for this strain development programme have been described previously (Simpson & Caten, 1979). Three mutagens -ethyl methanesulphonate (EMS), near-ultraviolet light in the presence of 8-methoxypsoralen (8MOP) and N-methyl-N'-nitro-N-nitrosoguanidine (NTG) -were used in these preliminary experiments.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Preliminary experiments designed to facilitate the choice of mutagen and mutation conditions for this strain development programme have been described previously (Simpson & Caten, 1979). Three mutagens -ethyl methanesulphonate (EMS), near-ultraviolet light in the presence of 8-methoxypsoralen (8MOP) and N-methyl-N'-nitro-N-nitrosoguanidine (NTG) -were used in these preliminary experiments.…”
Section: Introductionmentioning
confidence: 99%
“…This combination of mutagens has the added advantage that in Eschericlzia coli at least they act through different mutational pathways, 8MOP being dependent upon a functional exrA+/recA+ system while EMS is not (Bridges, 1976). Studies of the dose-response relationship for the production of titre-increasing mutants by 8MOP and EMS suggested that mutant frequency was largely independent of dose over the range giving 28 to 404, survival but declined at survivals of less than I (Simpson & Caten, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations